2020
DOI: 10.1007/s00701-020-04540-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of large and giant intracranial aneurysms according to various treatment modalities

Abstract: Purpose This study aimed to compare the treatment outcomes of large (15-25 mm) and giant (> 25 mm) intracranial aneurysms (IAs), according to different treatment modalities. Methods In total, 112 patients with large and giant IAs treated with various treatment modalities between January 2009 and December 2018 were retrospectively reviewed. Clinical and radiological parameters were analyzed and correlated with the treatment modality. Results A total of 141 procedures were performed on 112 patients. We initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“… 9 We thought that the complication rate was relatively high in this study for the following reasons: 1) we treated large and giant IAs with the maximal diameter larger than 15 mm, except for three fusiform aneurysms; and 2) the proportion of non-ICA locations, including the middle and anterior cerebral arteries (n=11, 33.3%), was relatively high. Choi, et al 18 have reported that the complication and mortality rates of FDS for large and giant IAs in a single-center series were 18.7% and 8.3%, respectively. These results were similar to the findings of the current study, as the indication for the use of FDS is the same in our country.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 9 We thought that the complication rate was relatively high in this study for the following reasons: 1) we treated large and giant IAs with the maximal diameter larger than 15 mm, except for three fusiform aneurysms; and 2) the proportion of non-ICA locations, including the middle and anterior cerebral arteries (n=11, 33.3%), was relatively high. Choi, et al 18 have reported that the complication and mortality rates of FDS for large and giant IAs in a single-center series were 18.7% and 8.3%, respectively. These results were similar to the findings of the current study, as the indication for the use of FDS is the same in our country.…”
Section: Discussionmentioning
confidence: 97%
“…However, additional coil packing is not permitted in South Korea, as we previously described. 18 Strict blood pressure control to lower direct hemodynamic stress on aneurysm wall and steroid therapy to reduce thrombus-related inflammation can be used to avoid this fatal complication. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most considerable discrepancy in the rate of occlusion between clipping and coiling occurs in the treatment of large (15-25 mm) and giant aneurysms (>25 mm). A retrospective study published in 2020 by Choi et al analyzing 112 patients with large and giant aneurysms found the complete occlusion rate after coiling to be just 36.3%, compared to 90.9% in the surgical group [ 79 ]. Thus, recurrence and retreatment rates were also significantly high at 46.8% and 31.9%, respectively.…”
Section: Reviewmentioning
confidence: 99%
“…The rapid development of endovascular treatment techniques has expanded the indications for the treatment of intracranial aneurysms [25], but at present, some aneurysms are better suited for surgical clipping. For example, for wide-necked aneurysms, no subsequent treatment of double antiplatelet due to stent implantation during endovascular treatment is required after surgical clipping; for patients with obvious intracranial hemorrhage, the hematoma can be removed and decompressed at the time of surgical clipping, or the hemorrhagic cerebrospinal uid can be fully released to reduce the incidence of vasospasm and hydrocephalus; clipping and shaping of giant aneurysms can achieve a great effect; and surgical clipping is still a better option for patients with intracranial arterial tortuosity and for aneurysms that are hard to reach with the catheter guide wire [5,22,23,35]. For long-term e cacy, endovascular treatment still has a certain recurrence rate.…”
Section: Comparison Of the Keyhole Approach And Conventional Craniotomymentioning
confidence: 99%